حكم التعاقد الإلكتروني باستخدام المستجيب الآلي وقت صلاة الجمعة: Electronic contracting on Jummah prayer time using auto responder - Al-Sa’e, Muaz Mohammad Faraj; Jibo, Salihu Musa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تأتي هذه الدراسة لبيان حكم العقد الإلكتروني عن طريق استخدام المستجيب الآلي وقت صلاة الجمعة، والهدف من هذا البحث هو بيان حكم هذه المسألة التي قد انتشرت بشكل كبير في زماننا، وبيان الصور التي قد تقوم بها هذه العقود، وحكم كل صورة من صورها، من خلال قوله تعالى: "يا أَيُّهَا الَّذِينَ آمَنُوا إِذَا نُودِي لِلصَّلَاةِ مِن يَوْمِ الْجُمُعَةِ فَاسْعَوْا إِلَى ذِكْرِ اللَّهِ وَذَرُوا الْبَيْعَ ذَلِكُمْ خَيْرٌ لَّكُمْ إِن كُنتُمْ تَعْلَمُونَ" [الجمعة:9]، فقمت باستقراء أقوال الفقهاء المتقدمين والمعاصرين في المسائل المتعلقة بالبيع وقت صلاة الجمعة، مبينا صور وقوع هذه المسألة قديما، كما قمت باستقراء أقوال المعاصرين في أنواع التعاقدات الإلكترونية وصورها، ثم قمت بتحليل هذه الأقوال لإبرالز علاقتها بمسألة البحث، وبعدها اتبعت المنهج الاستنباطي للوصول إلى حكم المسألة، والذي بينت فيه أن للمسألة صور متعددة منها الجائزة، والتي تنشأ ممن لا تجب عليه الجمعة، ومنها المحرمة، والتي تنشأ عن من لزمته صلاة الجمعة مع التفصيل فيها. ABSTRACT This study examines the ruling on electronic contracting through the use of automated responders during Friday prayer. The objective is to clarify the legal status of this issue, which has become widespread in contemporary times, and to present the various forms such contracts may take along with the ruling pertaining to each. The study is based on the Qur’anic verse: “O you who have believed, when the call is made for prayer on Friday, then proceed to the remembrance of Allah and leave trade; that is better for you, if you only knew” (al-Jumuʿah 9). I surveyed the opinions of both classical and contemporary jurists regarding sales conducted during Friday prayer, outlining how this matter occurred historically, and then examined modern scholarly views on different types and forms of electronic contracts. I subsequently analyzed these positions to demonstrate their relevance to the research question, before applying a deductive approach to arrive at the legal ruling. The conclusion shows that this issue has multiple scenarios, some permissible—when arising from one not obligated to attend Friday prayer—and others impermissible, when arising from one upon whom Friday prayer is obligatory, with detailed distinctions provided.